Interner en République : le cas de la France en guerre d’Algérie - Sylvie Thénault (Amnis)
During the Algerian War, the french government used exceptional measures against the Algerian nationalists, like, for example, internment. That is an arbitrary practise, in a dictatorship, but the republican regime is characterized by three important differences : this practise remains unusual ; there must be a legal system to organize internment ; writing, speaking about the camps or protesting against them is possible.